Space : the next twenty-five years - McDonough, Thomas R. (New York : Wiley, 1987)
Examines U.S. space science through the next twenty-five years, from manned spaceflight and military research to new technologies.
Includes index.
Bibliography: p. [221]-228.
Young Adult.
Keywords: Astronautics; Astronautics; Outer space -- Exploration; Outer space -- Exploration